Quaternized trimethyl functionalized chitosan based antifungal membranes for drinking water treatment. (1st March 2019) - Tabriz, Ayesha; Ur Rehman Alvi, Muhammad Azeem; Khan Niazi, Muhammad Bilal; Batool, Mehwish; Bhatti, Muhammad Faraz; Khan, Asim Laeeq; Khan, Asad U.; Jamil, Tahir; Ahmad, Nasir M.
Graphical abstract: Highlights: Quaternized trimethyl chitosan (TMC) was functionalized for waste water treatment. TMC was synthesized via reductive alkylation and methylation. The reduction in contact angle increases the surface wettability. The functionalized membranes had shown noticeable antifungal activity. Highest water flux of 1400 L/m 2 .h was observed for maximum TMC content. Abstract: Chitosan was functionalized to synthesize Quaternized N -trimethyl chitosan (TMC) and incorporated in polyethersulfone (PES) polymer to fabricate membranes for enhanced antifungal activity and water treatment. The TMC was synthesized from chitosan via reductive alkylation and methylation. The effect of concentration of chitosan and TMC on the properties of functionalized PES membranes was investigated. The membrane with the lowest concentration of TMC 5% (w/w) resulted in the largest average pore size than the PES membrane without chitosan or TMC. The surface wettability was enhanced as contact angle was reduced from 90° to 57° by increasing concentration of TMC to 15% (w/w). The resultant membranes exhibited improved water hydrophilicity, permeability and inhibition against fungal species. The functionalized membranes had shown noticeable antifungal activity against Aspergillus niger in the case of 15% TMC with 72% antifungal activity and 15% chitosan with 63% antifungal activity against Fusarium solani.